Settlement of bored piles with expander body system in lateritic soils - Monteiro,Fernando Feitosa (2021)
Abstract The Expander Body pile (EB) is a combination of a cast-in-situ pile method with an inflated, pump-grouted tip. The EB system's pioneering conjunction with the conventional drilling pile technique has improved work load, foundation security, cost reductions and abrupt displacements in lateritic, porous, unsaturated soils. The aim of this article is to analyze settlement estimates of bored piles equipped with the Expander Body System on tropical lateritic soil, using a deformability modulus obtained from laboratory and field tests. The piles were subjected to compression and uplift load tests. In addition, the estimates of the pile settlement are compared with the measured values, and the findings are discussed. The results strongly support that PMT and SPT tests present the optimal ratios between the measured and estimated settlements for both bored piles and bored piles with the Expander Body System. It can also be observed that CPT tests presented reasonable estimates for tensioned piles. Ultimately, it is verified that straightforward elastic models for the settlement assessment of bored piles can be used reliably in practice for piles equipped with the Expander Body System on tropical unsaturated soils.